Peran Benteng Rotterdam dalam Menarik Wisatawan Asing dan Mendorong Aktivitas Ekonomi di Makassar - Santi; Faiz Fauzan; Nurrahma; Rasti; A. Muh. Washiyyatun Hidayat; Putri Nabila; Mawar Ayu Cahyani; Huspa Arianna; Reski Ardilla Putri; Andi Nur Afiqa; Juwita Wulandari; Nurafifah sahib; Agus salim HR (Prodi Manajemen Universitas Syekh Yusuf Al Makassari Gowa, 2026)
Fort Rotterdam is a prominent historical tourist attraction in Makassar city that has significant cultural, historical, and architectural values. This study aims to examine the role of Fort Rotterdam in the tourism industry to attract international tourists and identify factors that increase its attractiveness. This study uses a qualitative method with a descriptive approach. Data were collected through field observations, interviews with managers and visitors, and relevant documentation studies. The results of the study indicate that Fort Rotterdam plays an important role in improving the image of Makassar's cultural tourism through preserving historical heritage, organizing cultural events, and providing educational facilities for tourists. The uniqueness of its colonial architecture, the presence of the La Galigo Museum, and its strategic location are key factors that attract international tourists to visit. In addition, promotions through digital media and government support also contribute to increasing tourist visits. Therefore, Fort Rotterdam not only functions as a historical site but also as a valuable asset in the tourism industry that can increase the attractiveness of the destination and support tourism growth in Makassar.